Conferimento della Laurea magistrale ad honorem in scienze archivistiche e biblioteconomiche a Michele Casalini / Award of the Laurea magistrale ad honorem in Library and information Science to Michele Casalini - Casalini, Michele (Lectio Magistralis, 2019)
On the 21st May 2019, the University of Florence awarded Michele Casalini an honorary degree for his dedication and his important contribution in the field of Library and Archival Sciences. The ceremony, which was held in the Rectorate's Aula Magna in Florence, represents the first recognition of merit for modern library science and the second for library and archival sciences to ever be granted by an Italian university. The text features the complete speeches by Luigi Dei, Rector, by Andrea Zorzi, Director of the SAGAS Department, the Laudatio by Mauro Guerrini, president of the Degree in Library and Archival Sciences and the Lectio Doctoralis by Michele Casalini, entitled La centralità delle biblioteche per il progresso e la democrazia. All the texts are published in Italian and English.